HAGIOLOGICAL PERSPECTIVE OF THE FATIMA MESSAGE - Katarzyna Parzych-Blakiewicz (Forum Teologiczne, 2018)
This paper presents a theological analysis of the content of the Fatima message, carried out according to hagiological assumptions. The analysis of Fatima sources, taking into account the aspect of hagiological research, made it possible to claim that holiness granted by Divine grace grows in a human being at the stage of his or her earthly life. Human history should develop the salvific course through cooperation between the human being and God upon the principle of dialogical relations. In the dialogue of salvation, God gives His grace to a human being, which is necessary to create a culture favouring the development of humanity, i.e. humanizing. Dialogical activity means acting in accordance with the theological hierarchy of values. The effects of dialogical cooperation are perceived in humanism favouring the improvement of humanity in the human person, humanity modelled on the humanity of Jesus Christ. The Marian aspect in the hagiological perspective is seen as a guideline showing the right direction of required historico-salvific changes.